Control of Microthrix parvicella and sludge bulking by ozone in a full-scale WWTP - Levén, Lotta (Water science and technology : a journal of the International Association on Water Pollution Research, 2016)
Bulking and rising sludge are common problems in wastewater treatment plants (WWTPs) and are primarily caused by increased growth of filamentous bacteria such as Microthrix parvicella. It has a negative impact on sludge settling properties in activated sludge (AS) process, in addition to being responsible for foam formation. Different methods can be used to control sludge bulking. The aim of this study was to evaluate the dosage of on-site generated ozone in the recycled AS flow in a full-scale WWTP having problems caused by M. parvicella. The evaluation of the experiment was assessed by process data, microscopic analysis and microbial screening on the experimental and control line before, during and after the period of ozone dosage. The ozone treatment resulted in decreased abundance of M. parvicella and improved the settling properties, without impairing the overall process performance. Both chemical oxygen demand (COD)- and N-removal were unaffected and the dominant populations involved in nitrification, as analysed by fluorescent in situ hybridization, remained during the experimental period. When the ozone treatment was terminated, the problems with sludge bulking reappeared, indicating the importance of continuous evaluation of the process